Speaker identification using artificial neural network by combination of resilent back-proagation and gradient descent /Cheang Soo Yee - Cheang, Soo Yee, 1985; Abdul Manan Ahmad; Fakulti Sains Komputer dan Sistem Maklumat (2009)
Thesis (Sarjana Sains (Komputer Sains)) - Universiti Teknologi Malaysia, 2009